Peningkatan Kemampuan Menulis Teks Berita dengan Menggunakan Model Pembelajaran Jigsaw Siswa Kelas VII UPTD SMP Negeri 3 Gunungsitoli Alo’oa - Gea, Indah Permata Sari; Zega, Imansudi; Halawa, Noibe; Bawamenewi, Arozatulo (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve the news writing skills of seventh grade students at UPTD SMP Negeri 3 Gunungsitoli Alo'oa through the application of the Jigsaw learning model. The type of research used is Classroom Action Research (CAR) which was carried out in two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through observation of student activities, observation of teaching and learning activities by teachers, and news writing tests. Data were analyzed descriptively, qualitatively, and quantitatively by comparing the results of each cycle. The results of the study showed an increase in learning activities and news writing skills. The average score for news writing in cycle I was 52.89 (sufficient category), while in cycle II it increased to 81.39 (good category). Thus, the use of the Jigsaw learning model is effective in improving students' news writing skills.